Pengaruh Terapi Latihan Menggunakan Media Audiovisual Terhadap Tingkat Perbaikan Respiratory Rate Pada Pasien COVID-19 - Agus Purnomo Rijal Kurniawan; Fransisca Xaveria Hargiani; Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:    RSPAL Dr Ramelan Surabaya is a Covid-19 Referral Hospital. It was recorded that from March 2020 to July 2021, more than 425 people have been treated for confirmed Covid-19. The number of dead cases has exceeded 63 people and the recovery rate is 85% (362 people). The integrated handling of Covid-19 patients is manifested in a Covid-19 task force which involves the participation of Health Workers including Physiotherapists. The availability of Physiotherapists, which only numbered 14 people, was faced with the increasing number of referred Covid-19 patients. Respiratory rate (RR) or commonly referred to as respiratory rate is defined as the number of breaths taken by a person in one minute or the number of breath cycles per minute. This method aims to assess whether or not a person is difficult to breathe.Methods:    This research is important to do to determine the effect of exercise therapy using audiovisual media on the respiratory rate improvement in Covid-19 patients. So that this method can be the right choice in handling patients during the Covid-19 pandemic, can provide optimal, effective and efficient results, as well as comfortable and safe. This research is experimental using One Group Pretest and Posttest. The sample population of this study was 25 confirmed Covid-19 patients who met the inclusion and exclusion criteria, treated in a special room for treating Covid-19 patients.Results:    Statistical analysis shows the t-count value in the sample test with data that is normally distributed where the significance level of 5% or 0.05 is in the significant area. The test results show that the absolute t-count value is greater than the t-table value, which is 7.96 > 2.064.Conclusion:  Therefore, it can be concluded that there is an effect of exercise therapy using audiovisual media on improving the respiratory rate in Covid-19 patients at Dr Ramelan Hospital Surabaya.